Multinational resilience or dispensable jobs? German FDI and employment in the Czech Republic around the Great Recession. - Eisermann, Merlind; Moritz, Michael; Stockinger, Bastian (Nürnberg, 2015)
"This article investigates the employment development of Czech-based firms in German ownership in the years around the Great Recession of 2008/2009. The intense involvement of German firms in the economy of the neighboring country via foreign direct investment (FDI) raises the question whether under the conditions of a historically deep global downturn, Czech employees in multinational companies were confronted with an increased volatility of their jobs. Using a unique firm-level dataset, we contrast the affiliates of German investors with purely Czech-owned enterprises. Our findings indicate that in the years before the crisis, firms with German capital exhibited a noticeably more positive employment development. The results from the year 2008 onwards give reason to the conclusion that German-owned firms played a stabilizing role for the Czech labor market during the recession."